Structural and Morphological Observations on Tungsten Oxide Hydrates Ged to Room Temperature in Alkali Containing Queous Environment - Balazsi, Csaba; Pfeifer, Judit (Communications - Scientific letters of the University of Zilina, 2001)
The room temperature ageing process of tungsten oxide hydrate (H2WO4.H2O) grains prepared by the methods of Freedman [J. Am. Chem. Soc. 81 (1959) 3834.] ([Na]residual 10ppm)) and Zocher and Jacobson [Kolloidchem. Beih. 28-6 (1929) 167.] ([Na]residual 100ppm) has been studied. A comparison between two preparation methods and ageing characteristics is given. It is found that spindle shaped – Zocher type grains have a strong tendency to morphological conversion depending on pH value of surrounding aqueous solution. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) studies have shown that the high structural and morphological stability of Freedman type grains can be altered by presence of alkali ions. Moreover, some incorporation of cations was observed.